Ustalenie struktury finansowania przedsiębiorstwa na podstawie modelu zdyskontowanych przepływów środków pieniężnych oraz skorygowanej wartości netto - Słoński, Tomasz (The Estimation of Capital Structure Based on DCF and APV Models, 2005)
In the Discounted Cash Flow (DCF) method strict assumptions about capital structure are hold. Therefore, in some cases the usage of this method may lead to large errors in a firm's valuation. The Adjusted Present Value method (APV) estimates firm's value without any assumptions about capital structure and this method. In this article the capital structure estimation based on the iteration method is presented. The iteration method uses both DCF and APV methods.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 174-183